Lighting and fan control using PIC: article - Ahmad Diniah, Najihah; Ibrahim, Mahmud (2008)
This paper describe the design of automatic control of fan and lighting of a room depending on the occupancy. The light and fan will be 'ON' whenever the room is not empty. If temperature will be controlled to a set temperature when the room is vacant and the system will shut down automaticalty. Motion sensor, Passive Infraed (PIR), temperature sensor and Peripheral Irterface Controller (PIC) ae integrated to detect status of the occipancy and the room temperature and then control the room ambient temperature.